PERTANGGUNGJAWABAN PARTAI TERHADAP CALON ANGGOTA LEGISLATIF YANG MELAKUKAN TINDAK PIDANA PEMILU (Accountability of Party Against Legislative Candidates Who Conduct Criminal Act of Election) - Mohd Din; Ida Keumala Jeumpa; Nursiti Nursiti (Jurnal Penelitian Hukum De Jure, 2016)
This research aimed to study how the party`s accountability for offences committed by legislative candidates. What action that taken by a party of electoral violations and whether the party can be charged for. In the doctrine of Criminal Law known by criminal responsibility related to offenders, and in progress subject to criminal law, not only individual but institution or agency or corporation/firms. So, they should be responsible for it. It was a normative legal research, studying the principles of law related to criminal responsibility. Collecting data were done by two stages that were literature and field research. The first aimed to obtain secondary data namely, law material ;primary, secondary and tertiary. And then, the second, collecting data with an in-depth interview with certain key informant. It used a qualitative method.The result showed that party never asked for their responsibility related to offences by legislative candidates who committed election crime because the act did not rule it. The party had not take action associated with offences were done by them. Politic party as cooperation/firms ideally should take account to candidates who conducted the crime. It was a necessary regulation that managed its accountability as in cooperation. Besides, the party should give politics education and strict sanctions to them who did despicable manners.